Concerns for Digital Privacy in Business and Management: An overview and Future Discourses Recommendation - Linando, Jaya Addin; Herwanto, Guntur Budi (Association for Scientific Computing Electrical and Engineering, 2022)
This paper aims to highlight the developing awareness of concern for digital privacy from business and management viewpoint. The authors compile data privacy literature in management field and visualize the literature into 4 main clusters of concerns. The 4 main cluster of concerns in data privacy discourse on management field are: internet; roles-trust-security; locations; and consumer privacy. This paper contributes on the development of research and discourse in data privacy and management domain. Besides delivering the overviews of the digital privacy concerns in business and management fields, the paper also places suggestions for future researchers.